Evaluating blended learning effectiveness: an empirical study from undergraduates’ perspectives using structural equation modeling - Han, Xiaotian (Frontiers in Psychology, 2023)
Following the global Covid-19 outbreak, blended learning (BL) has received increasing attention from educators. The purpose of this study was: (a) to develop a measurement to evaluate the effectiveness of blended learning for undergraduates; and (b) to explore the potential association between effectiveness with blended learning and student learning outcomes. The study employed a non-experimental, correlational design and solicited survey responses from undergraduates to address the research questions in two phases. Biggs’ constructive alignment theory (2003) was taken as the theoretical framework upon which this study was based. The measurement of the blended learning was developed in 6 sub-scales with a total of 25 items. Specifically, course marks were used as an indicator of students’ learning outcomes. The results illustrated that: (a) The hypothesized components positively contributed to the model; and (b) There is a positive correlation between effectiveness with blended learning and student learning outcomes in higher education.